2021
DOI: 10.1016/j.msard.2021.103264
|View full text |Cite
|
Sign up to set email alerts
|

Acting centrally or peripherally: A renewed interest in the central nervous system penetration of disease-modifying drugs in multiple sclerosis

Abstract: With the recent approval of cladribine tablets, siponimod and ozanimod, there has been a renewed interest into the extent to which these current generation disease-modifying therapies (DMTs) are able to cross into the central nervous system (CNS), and how this penetration of the blood-brain barrier (BBB) may influence their ability to treat multiple sclerosis (MS).The integrity of the CNS is maintained by the BBB, blood-cerebrospinal fluid barrier, and the arachnoid barrier, which all play an important role in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 153 publications
0
13
1
Order By: Relevance
“…Almost all pathogenetic MS treatments affect Th17 cell function [ 8 ]. The effect of these treatments on immune cells in the CNS still needs to be clarified, suggesting the relevance of the new therapeutic approaches that allow the modulation of the Th17 immune response directly in the CNS [ 9 ]. In this regard, the effect of catecholamines on Th17 cells has attracted increasing attention.…”
Section: Discussionmentioning
confidence: 99%
“…Almost all pathogenetic MS treatments affect Th17 cell function [ 8 ]. The effect of these treatments on immune cells in the CNS still needs to be clarified, suggesting the relevance of the new therapeutic approaches that allow the modulation of the Th17 immune response directly in the CNS [ 9 ]. In this regard, the effect of catecholamines on Th17 cells has attracted increasing attention.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note, that antidepressants can affect inflammation directly in the CNS, while the ability of monoclonal antibodies to migrate through blood-brain barrier is limited, which suggests their effect primarily on the periphery ( 66 ). In this regard, the potential ability of antidepressants to modulate Th17-mediated neuroinflammation in MS has drawn a great attention.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have indicated that cladribine has the potential to penetrate the CNS and achieve a concentration in the cerebrospinal fluid of up to 25% of its concentration in plasma [ 28 – 30 ], which raises the possibility that cladribine tablets may be able to reduce lymphocyte numbers within the CNS as well as those circulating in the periphery [ 31 , 32 ]. However, a need exists to better understand if the potential for direct effects of cladribine within the CNS are clinically significant in terms of additional benefits over and above treatment effects on peripheral immune cells [ 33 ].…”
Section: Cladribine Mechanism Of Action and Lymphocyte Selectivitymentioning
confidence: 99%